2020
DOI: 10.1177/1556984520911025
|View full text |Cite
|
Sign up to set email alerts
|

Left Anterior Mini-Incision for Pulmonary Valve Replacement Following Tetralogy of Fallot Repair

Abstract: Pulmonary insufficiency is a known complication following Tetralogy of Fallot repair. With over 90% of patients now surviving to adulthood, surgeons are once again faced with the question of when, and more importantly, how to reintervene. We developed a novel approach to pulmonary valve replacement in this population through a 5-cm left anterior mini-incision. The incision is optimized for exposing and operating on the right ventricular outflow tract and the main pulmonary artery in patients with a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
(16 reference statements)
1
14
0
Order By: Relevance
“…Vekstein et al 13 reported LAMI in a 12‐year‐old male with TOF. We agree with others that patients who are candidates for this procedure should be at least 30 kg in weight to allow safe groin vessel cannulation 12 . These patients are young with normal aorta and peripheral vasculature, which allow safe utilization of peripheral cannulation for CPB.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Vekstein et al 13 reported LAMI in a 12‐year‐old male with TOF. We agree with others that patients who are candidates for this procedure should be at least 30 kg in weight to allow safe groin vessel cannulation 12 . These patients are young with normal aorta and peripheral vasculature, which allow safe utilization of peripheral cannulation for CPB.…”
Section: Discussionsupporting
confidence: 71%
“…Nellis et al 12 have recently reported a series of seven patients with the previous repair of TOF who underwent LAMI for PVR with excellent results. The authors' median CPB time was 2.5 h, and two patients experienced early complications.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, surgical closure from LALT is preferred in such patient groups. Recently, this LALT incision was also applied to replace pulmonary valve in 7 patients following Tetralogy of Fallot repair by Nellis et al (23) The lower weight limit of femoral cannulation is inconsistent. Most surgeons prefer using peripheral cannulation in patients over 30 kg; however, surgeons from Switzerland dissected iliac artery in infants with body weight as low as 10 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Since late 2018, our group has performed 19 operations, including 14 redo PVRs following primary tetralogy of Fallot repair, through a 5-cm left anterior mini-incision. 3,4 In our series, the median age for patients undergoing left anterior mini-incision was 16 years old (13-23 years) with a median body mass index of 20 (19-29). Two patients with body mass indexes of>30 and multiple previous median sternotomies were converted to sternotomy due to dense adhesions and inadequate exposure.…”
mentioning
confidence: 81%